Being a pregnant woman in the repellent environment: guidelines, preventive measures and anxiety in front of the positive diagnosis for the Zika Virus - Sousa Alves, Jheynny (2018)
The aim of this research was to identify the guidelines received in prenatal care, the preventive measures used against Zika virus infection and the level of anxiety of pregnant women with a positive diagnosis of Zika infection. A descriptive and exploratory research with a quantitative approach was carried out. Participants were 53 pregnant women users of the prenatal service of Pontal do Araguaia-MT. The semi-structured interview and the Trait-State Anxiety Inventory (IDATE) were used as instruments for data collection. Data analysis was performed using simple descriptive statistics. The pregnant women received information about the Zika Virus in a higher frequency of health professionals during the prenatal consultations, with the nurses identified as health promoters, the greatest disseminators of knowledge and empowerment of pregnant women. Most make use of preventive measures, being the use of the repellent and the cleaning of the yard the most frequent ones. Pregnant women who had a positive diagnosis for Zika Virus had high anxiety / Trace / State scores. It was concluded that the qualified guidance on zika virus in prenatal care is fundamental to the reduction of anxiety, and that it is the health professionals who empower pregnant women against the repellent environment.